Two flags over Iwo Jima : solving the mystery of the U.S. Marine Corps' proudest moment - Hammel, Eric M. (Casemate, 2018)
"An authoritative look at an event that has taken on a legendary status ... [an] essential history for those wanting the truth behind the legend" (Publishers Weekly). Joe Rosenthal's "Raising the Flag on Iwo Jima" photo is one of the best-known images of US war history'and a powerful symbol of patriotism. But the story of how the flag got there, and even the identity of the soldiers in the photo, has been muddied by history. Here, military historian Eric Hammel sets the record straight'viewing complex events through the lens of the story of the infantry company in which all the flag raisers served. The photo captures the moment that the first American flag flew over the core of Imperial Japanese territory on the top of Mount Suribachi. The focus of this book lies on the 28th Marine Regiment's self-contained battle in February 1945 for Mount Suribachi, the 556-foot-high volcano on Iwo Jima. It was here that this one regiment defeated more than 1500 heavily armed Japanese combatants who were determined to hold the highest vantage point on the island. Two Flags over Iwo Jima reveals the all-but-forgotten first flag raising and the aftermath of the popularization campaign undertaken by the post-WWII Marine Corps and national press. Hammel attempts to untangle the various battles that led up to the first and second flag raisings, as well as follow the men of the 28th Marine Regiment in the events that took place after. The full story behind one of the most iconic photographs ever taken is revealed'along with the real heroism and stories of the men behind a dramatic moment captured in time. "A richly illustrated account ... A must for World War II buffs." 'Kirkus Reviews (starred review)